2016
DOI: 10.1093/gerona/glw214
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean Diet Supplemented With Coenzyme Q10Modulates the Postprandial Metabolism of Advanced Glycation End Products in Elderly Men and Women

Abstract: Advanced glycation end products (AGEs) and oxidative stress are elevated with aging and dysmetabolic conditions. Because a Mediterranean (Med) diet reduces oxidative stress, serum AGEs levels, and gene expression related to AGEs metabolism in healthy elderly people, we studied whether supplementation with coenzyme Q10 (CoQ) was of further benefit. Twenty participants aged ≥ 65 (10 men and 10 women) were randomly assigned to each of three isocaloric diets for successive periods of 4 weeks in a crossover design:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 40 publications
1
39
1
1
Order By: Relevance
“…The increased level of lung HMGB1 was positively correlated with diet‐associated AGEs but not, surprisingly, aging‐associated AGEs (Bartling et al., 2007). Elderly people underwent 4 weeks of dAGEs restriction, the expression level of RAGE in the peripheral blood mononuclear cells was decreased (Lopez‐Moreno et al., 2018; Lopez‐Moreno et al., 2016). A similar reduction in RAGE secretion was also observed in type‐2 diabetic patients, whereas, not in healthy overweight individuals taking the same low‐AGE diets (Uribarri et al., 2011).…”
Section: In Vivo Metabolism Of Dagesmentioning
confidence: 99%
“…The increased level of lung HMGB1 was positively correlated with diet‐associated AGEs but not, surprisingly, aging‐associated AGEs (Bartling et al., 2007). Elderly people underwent 4 weeks of dAGEs restriction, the expression level of RAGE in the peripheral blood mononuclear cells was decreased (Lopez‐Moreno et al., 2018; Lopez‐Moreno et al., 2016). A similar reduction in RAGE secretion was also observed in type‐2 diabetic patients, whereas, not in healthy overweight individuals taking the same low‐AGE diets (Uribarri et al., 2011).…”
Section: In Vivo Metabolism Of Dagesmentioning
confidence: 99%
“…As a coadjuvant therapy, it has been assessed alongside the Mediterranean diet in elderly population, and when 200 mg of CoQ10 per day was added, the oxidative and inflammatory states were diminished compared to the Mediterranean and Western diets [186]. A liquid formulation with ubiquinol 100 mg/day was given over 12 weeks in T2DM patients showing increased levels of antioxidant biomarkers like SOD, catalase, and GPx, but not MDA, compared to placebo [187], compared to a similar study done in patients with T2DM and DN where MDA and AGEs levels were diminished [188].…”
Section: Polyphenols: Anthocyanins and Resveratrolmentioning
confidence: 99%
“…22 Several studies have shown the relation between dietary AGEs and outcomes related to CVD. [23][24][25][26][27][28][29] In animal studies, Poulsen et al showed that a high-AGE diet in rats increased RAGE expression, 27 while CML-enriched diets induced endothelial dysfunction and accelerated the development of arterial aging. 23 Consumption of a high-AGE meal increased inflammatory markers (intercellular adhesion molecule 1 and vascular cell adhesion molecule 1 levels) and decreased significantly flow-mediated dilatation and microvascular function in both diabetic and nondiabetic individuals.…”
mentioning
confidence: 99%
“…32 Recently, our research group suggested that the Mediterranean diet could be a "good example" of a low-AGE diet providing a low content of AGEs during its consumption, thus reducing circulating AGEs (CML and MG), modulating the gene expression of the RAGE and AGER1, and suppressing oxidative stress/inflammation markers in both patients with the metabolic syndrome and in the elderly population. [24][25][26] Although dietary AGE restriction seems to be a simple and efficient strategy to reduce circulating AGEs and improve different CVD risk factors, additional studies are needed before dietary recommendations could be made. Unfortunately, there are no prospective studies linking dietary AGE with cardiovascular events since all available data are related to crosssectional clinical studies.…”
mentioning
confidence: 99%